(untitled) (Global Journal of Science Frontier Research, 2014)
In order to study the effect of intercalation of LiAl on the cation distribution and properties of Fe 2 TiO 5 , the samples are prepared by standard ceramic technique. The singlephase formation of the pseudobrookite is confirmed by XRD technique. The retention of amount and proportion of LiAl in the ceramics is confirmed by ICP technique. The ac and dc resistivity of the ceramic increases considerably whereas the interfacial contribution to the dielectric constant decreases by intercalation of LiAl. The experimental data of relaxation spectra, variation of dielectric constant and resistivity with temperature is analyzed and correlated. The magnetic hysteresis and susceptibility measurement shows that LiAl enhances the long range magnetic ordering. The proposed empirical model determines the cation distribution of the samples using lattice parameters.